1983
DOI: 10.1177/036354658301100308
|View full text |Cite
|
Sign up to set email alerts
|

Rotational motion of the knee*

Abstract: This study deals with the quantitation of axial rotation at the knee. Passive rotation of the knee was measured at various degrees of flexion on 17 subjects with normal knees and 19 patients with unilateral anterolateral rotatory instability. Normal subjects were found to have bilateral symmetric rotational knee motion at each angle of flexion tested. When the knee is in a position of flexion between 30 and 90 degrees, there are approximately 45 degrees external and 25 degrees internal rotation. Rotatory motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 15 publications
2
62
1
Order By: Relevance
“…Zarins et al [20] have measured knee rotation with the subject lying on one side. The knee was positioned and measured at angles of 90°, 60", 30", 15" and 5" of flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Zarins et al [20] have measured knee rotation with the subject lying on one side. The knee was positioned and measured at angles of 90°, 60", 30", 15" and 5" of flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric studies revealed that the section of the ACL led to 2.4 to 4°increase in rotation in knee flexion angles below 30° [ 69,70]. Above this degree of flexion, the increase in rotation induced by the lesion was not detectable anymore [25,71]. Early in vivo studies demonstrated a similar increase of rotation in the injured knee by 10 % (3°) compared to the healthy knee [72].…”
Section: Knee Laxity In the Injured Knee Diagnosis Of Acl Injuriesmentioning
confidence: 97%
“…Most researchers apply this torque from internal to external rotation or from external to internal rotation to obtain a complete cycle of rotation. A solution to avoid the hysteresis phenomenon, which comes along with this technique and influences the reproducibility of the measurements [25,26], is to perform separate measurements of internal and external rotation and to include Bpreconditioning trials.R otational knee laxity is influenced by the patient's position and by the location of rotation measurement. Knee rotation is higher if the knee is flexed at 90°compared to 20°and if the hip is extended compared to the flexed position at 90° [ 27].…”
Section: Static Rotational Knee Laxitymentioning
confidence: 99%
“…3 The effect on tibial rotation of cutting the ACL has been well reported. 4,5,6,7 In a cadaveric study, 4 total (internal and external) rotation at 10 and 30 degrees of knee " exion increased signi! cantly after the ACL was cut.…”
mentioning
confidence: 95%
“…9,10 Therefore, severing the ACL greatly increases the amount of tibial rotation. On the other hand, a study that compared ACL injured knees with normal knees by using a Cybex dynamometer 4 to measure rotational motion showed injured knees had signi! cantly greater external and internal rotation compared to normal knees (!…”
mentioning
confidence: 99%